Validation of key Arctic energy and water budget components in CMIP6 - Susanna Winkelbauer (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Michael Mayer (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Leopold Haimberger (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (Climate Dynamics, 2024)
The abstract is available here: https://uscholar.univie.ac.at/o:2067030 The abstract is available here: https://uscholar.univie.ac.at/o:2067030